1983
DOI: 10.1097/00004032-198308000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Radon and Cancer Correlations in Maine

Abstract: The distribution of 222Rn has been measured in the sixteen counties of Maine, U.S.A. by liquid scintillation counting of water samples from more than two thousand public and private wells. Three hundred and fifty of these wells have been characterized for geology and hydrology. Airborne radon has been measured in seventy houses with grab samples and in eighteen houses for 5-7 days each with continuously recording diffusion-electrostatic radon detectors. Concentrations of radon in water ranged from 20 to 180,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

1985
1985
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 0 publications
0
26
0
2
Order By: Relevance
“…The estimated average background y-radiation per county has also been used as a proxy for potential indoor radon, since there tends to be a rather strong correlation between y-radiation and emanation of radon from the ground (70). Some other more-or-less positive studies have been based on measurements of Ra-226 in water (71) or levels of radon in water and indoor air (72). Some correlation studies have come out negative with regard to lung cancer, for example, studies from Canada (73), China (74), and France (75).…”
Section: Studies Of Indoor Radon and Lung Cancermentioning
confidence: 99%
“…The estimated average background y-radiation per county has also been used as a proxy for potential indoor radon, since there tends to be a rather strong correlation between y-radiation and emanation of radon from the ground (70). Some other more-or-less positive studies have been based on measurements of Ra-226 in water (71) or levels of radon in water and indoor air (72). Some correlation studies have come out negative with regard to lung cancer, for example, studies from Canada (73), China (74), and France (75).…”
Section: Studies Of Indoor Radon and Lung Cancermentioning
confidence: 99%
“…Hess et al (15) have found that there is a correlation of radon in water supplies and radon in indoor air. This problem undoubtedly exists in other areas where deep wells are used for domestic water.…”
Section: Factors Modifying Radon In Homesmentioning
confidence: 99%
“…In Maine (15), artesian well water supplies in parts of the state have been found to have high concentrations of dissolved radon, and in some instances use of showers or dishwashers can increase indoor concentrations significantly. Hess et al (15) have found that there is a correlation of radon in water supplies and radon in indoor air.…”
Section: Factors Modifying Radon In Homesmentioning
confidence: 99%
“…As a result, very high radon concentrations can sometimes be found in associated water supplies. For example,s urvey of 222Rn concentrations in well-water in Maine found a range of 7 x 10 2 to 7 x 10 Bq/m 3 (20 to 180,000 pCi/l), while wells in granitic areas were found to average 8 x 10 5 Bq/m 3 (Hess et al 1983); and the average concentration in water from drilled wells in Finland has been found to be 6.3 x 10 5 Bq/m 3 (Asikainen and Kahlos 1980). With normal water use, the radon entering indoor air from water with such high concentrations can be expected to be significan t.…”
Section: Watermentioning
confidence: 99%